Integrative analysis of anti-breast CancerPotential of metabolites from Pseudomonas frederiksbergensis isolated from Taoerqi - Ma, Yuexing; Zheng, Haoyi; Liu, Simin; Yuan, En; Qiao, Xin; Dai, Zhang; Wu, Wenli; Pan, Rongbin (Frontiers in Pharmacology, 2025)
IntroductionThe Tibetan medicinal botanical drug Taoerqi has long been recognized for its anti-inflammatory, antibacterial, and tumor-inhibitory properties.MethodsBotanical drug focuses on the isolation and characterization of secondary metabolites from Pseudomonas frederiksbergensis, an endophytic bacterium isolated from Taoerqi roots. The metabolites were obtained through fermentation and purification processes and were evaluated for their anti-breast cancer activities using cellular assays and transcriptomic analysis. Key regulatory targets, including SARM1, RGS5, PROM2, and BAG1, were identified through bioinformatics analysis and validated using qPCR and Western blotting. Furthermore, a clinical risk assessment model was constructed using breast cancer transcriptome databases to explore the potential prognostic value of these targets.ResultsThe secondary metabolites from Pseudomonas frederiksbergensis exhibit significant anti-tumor effects and highlight their potential molecular mechanisms in breast cancer regulation.DiscussionThis study provides insights into the therapeutic potential of these metabolites and lays the groundwork for future preclinical and in vivo investigations.